Reducing HDAC6 ameliorates cognitive deficits in a mouse model for Alzheimer's disease. Issue 1 (26th November 2012) - Govindarajan, Nambirajan; Rao, Pooja; Burkhardt, Susanne; Sananbenesi, Farahnaz; Schlüter, Oliver M.; Bradke, Frank; Lu, Jianrong; Fischer, André
Abstract: Histone deacetylases (HDACs) are currently being discussed as promising therapeutic targets to treat neurodegenerative diseases. However, the role of specific HDACs in cognition and neurodegeneration remains poorly understood. Here, we investigate the function of HDAC6, a class II member of the HDAC superfamily, in the adult mouse brain. We report that mice lacking HDAC6 are cognitively normal but reducing endogenous HDAC6 levels restores learning and memory and α‐tubulin acetylation in a mouse model for Alzheimer's disease (AD). Our data suggest that this therapeutic effect is, at least in part, linked to the observation that loss of HDAC6 renders neurons resistant to amyloid‐β‐mediated impairment of mitochondrial trafficking. Thus, our study suggests that targeting HDAC6 could be a suitable strategy to ameliorate cognitive decline observed in AD. Abstract : The authors identified HDAC6 as a novel therapeutic target in Alzheimer's disease. Reducing HDAC6 protein levels in the brains of an AD mouse model improves memory and protects neurons against amyloid‐β‐induced impairment of mitochondrial trafficking.